Janus effects of NaCl on structure of egg yolk granules. (1st March 2022) - Li, Teng; Su, Huanhuan; Zhu, Jiaqian; Fu, Yuying
Highlights: NaCl disrupted calcium bridges and dissociated granules at pH 4–7. Dissociated granules re-aggregated with addition of NaCl at pH 2–3. Adsorption of highly hydrated Na + and Ca 2+ stabilized granule particles at pH 5–10. Adsorption of poorly hydrated Cl - failed to stabilize granule particles at pH 2–3. Granules might be used as delivery vehicles for hydrophobic bioactive compounds. Abstract: Egg yolk granules are supramolecular assembly of high-density lipoproteins and phosvitin driven by calcium bridges. However, applications of granules are severely restricted by the large particle size and poor water dispersibility. This study revealed the Janus effects of NaCl on structure of granules at varied pH values. Addition of 0.3–0.5 M NaCl led to the dissociation of at pH 5.0–7.0. At pH 5.0–10.0, dissociated granules demonstrated good colloidal stability with NaCl because of the adsorption of highly hydrated Na + and Ca 2+, which provided strong hydration repulsion when electrostatic repulsion was screened. In contrast, at pH 2.0 and 3.0, dissociated granules were positively charged with adsorption of poorly hydrated Cl - as counterions. Cl - failed to give sufficient hydration repulsion, leading to the phase separation with 0.3–0.5 M NaCl. Similar effects have been also found in LiCl, KCl, and CsCl, but Li + might be less effective to disrupt calcium bridges.